21 Does a one day hospice placement for medical students do more harm than good?. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Ward, Jason; Rayment, Clare; Hallam, Jennifer
Abstract : Background: In their first year as a doctor, F1s will care for 40 patients who will die and 120 patients in the last year of life. However, research shows junior doctors are often unprepared. We present data on the value of extending a hospice placement from 1 day to 4 days. Methods: Students were randomly allocated to 1 day or 4 days in 3 different hospices Students completed a thanatophobia scale, self-efficacy in palliative care scale and placement evaluation questionnaire. Performance in palliative medicine and oncology questions in end of year summative exams were compared. Results: 153 students undertook the 4 day placement. All students (1 and 4 day) had improved self- efficacy scores. 4 day placements had a greater effect on the global score and individual questions. Thanatophobia scores were reduced for the 4 day but not the 1 day placement. Students feedback was overwhelmingly positive highlighting the high quality of teaching, alignment of classroom and placement teaching, opportunities for work based assessments, medicines management, communication skills and interprofessional learning. 4 day students scored significantly higher in palliative medicine and oncology OSCE stations, higher for palliative medicine written questions, approaching significance in oncology written questions. Conclusions: Extending placements in hospices to 4 days significantly improved student's self-efficacy in palliative care and reduced thanatophobia when compared to a 1 day placement. Students valued the placements and as well as learning specific subject knowledge they developed many generic skills. 4 day students did better in both their oncology and palliative care OSCE stations and better in written palliative medicine questions. Students may have increased feelings of helplessness in caring for dying patients when they only attend a hospice for 1 day. Medical Schools should be encouraged to extend placements in palliative care and be aware for the potential increase in distress when only a short placement is provided.